PENGARUH GAYA BELAJAR VISUAL AUDITORIAL KINESTETIK TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MAN 2 DAN SD NEGERI 53 BANDA ACEH - Syauky, Ahmad; Jannah, Miftahul; Zulfatmi, Zulfatmi; Zubaidah, Zubaidah (Satya Widya, 2025)
Islamic Religious Education (PAI) has a strategic role in shaping students' religious character. However, the mismatch between learning methods and students' learning styles often becomes an obstacle in improving their understanding. This study aims to analyze the effect of visual, auditorial, and kinesthetic learning styles on students' understanding of PAI subjects at MAN 2 and SD Negeri 53 Banda Aceh. This study used a mixed method approach with a sequential explanatory design. Data were collected through questionnaires, observations, interviews, and documentation. The results showed that visual learning styles dominated in MAN 2 schools as much as 45%, and SD 53 as much as 50% and produced the highest understanding when students were assisted by image, video, and infographic media. Auditorial students in MAN 2 as much as 30%, and SD 53 as much as 27.5% better understand the material through lectures, discussions, and religious audio. Meanwhile, kinesthetic students in MAN 2 (25%) and SD 53 (22.5%) showed significant improvement during practice-based learning such as worship simulations and other motor activities. This research confirms the importance of an inclusive learning approach, by adapting teaching strategies to the diversity of students' learning styles to improve their understanding holistically. In addition, the results can serve as a reference in the preparation of differentiation-based teaching tools and the development of teacher training to be more responsive to the learning characteristics of learners at various levels of education.